1893 Okla. Terr. Stat. 504, ch. 25, art 45, § 7 - (:unkn) unknown (General Publisher, 1893)
Prohibits any person from carrying into any church, religious assembly, or assembly of public worship, amusement, or for educational or scientific purposes, or any circuis, show or public exhibition of any kind, or into any ball room, social party, or social gathering, or to any election, place where intoxicating liquors are sold, political convention, or any other public assembly. Applies to any pistol, revolver, Bowie knife, dirk knife, loaded cane, billy, metal knuckles, or any other offensive or defensive weapon.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES